Predicted effects of gender, physical activity and quality of life in internet addiction: university student sample - Saldıran, Tülay Çevik (Journal of Dependence, 2021)
Objective: The aim of this study was to investigate the relationship between the quality of life and physical activity of university students with internet addiction and to examine them according to gender differences.Methods: In this study, a total of 320 internet users of college students with ages ranging from 18 to 30 were recruited. To measure the level of ınternet addiction, the Internet Addiction Test was used. Based on the total test score, internet addiction was categorized as no addiction if the score was less than 49. International Physical Activity Questionaire-Short Form (IPAQ-SF) used in physical activity level assessment. Students were evaluated with the World Health Organisation Quality of Life Scale-BREF (WHOQOL-BREF) questionnaire, which examines the quality of life in 4 dimensions (physical health, psychological, social relations, and environment).Results: According to the UFAA scores, the students were individuals with low physical activity (2035.54±2205.39 MET-min/week). They were included in the asymptomatic (0-49) group with their Internet addiction level (33.10± 5.40). Physical health scores were higher in male students. There was no effect of physical activity on the ınternet addiction level. Physical health interacted negatively with internet addiction, while it had a positive effect on social relationships. If gender was controlled, internet addiction was negatively affected by physical health and the environment, and there was a positive correlation between social relations and internet addiction.Conclusion: Internet addiction was unrelated to gender or physical activity level however it was inversely related to the quality of life domains (physical health, environment), also was directly proportional to social relations.
Keywords: Internet addiction; physical activity; quality of life; college students